Meso-Cenozoic Brazilian Offshore Magmatism Geochemistry, Petrology, and Tectonics - Santos, Anderson Costa Dos; Santos, Anderson Costa Dos; Hackspacher, Peter Christian (Academic Press, 2021)
Meso-Cenozoic Brazilian Offshore Magmatism: Geochemistry, Petrology and Tectonics presents detailed studies from different points-of-view on the geological$1 (Bparticularly magmatic$1 (Bevolution of the Brazilian and South Atlantic Ocean offshore areas. This comprehensive book on geological events will help readers understand the holistic evolution of the area across geographical boundaries. Each chapter consists of an introduction, regional and local geology, methods, results, discussions, conclusions and supplementary material related to the geological development in island and seamounts in the Brazilian Platform and seafloor. - Integrates independent studies and research of the Brazilian offshore magmatism and tectonics into a single book - Includes new seamount and island data that was previously unavailable to the public - Introduces case studies to provide real-world examples of volcanism and scientific evolutions